2021
DOI: 10.37236/10225
|View full text |Cite
|
Sign up to set email alerts
|

Paths of Length Three are $K_{r+1}$-Turán-Good

Abstract: The generalized Turán problem ex$(n,T,F)$ is to determine the maximal number of copies of a graph $T$ that can exist in an $F$-free graph on $n$ vertices. Recently, Gerbner and Palmer noted that the solution to the generalized Turán problem is often the original Turán graph. They gave the name "$F$-Turán-good" to graphs $T$ for which, for large enough $n$, the solution to the generalized Turán problem is realized by a Turán graph. They prove that the path graph on two edges, $P_2$, is $K_{r+1}$-Turán-good for … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…For Conjecture 1.2, Murphy and Nir [16], and Qian et al [18]) have confirmed this conjecture for P 4 , P 5 and k ≥ 4, we continue to confirm this conjecture for P 6 and k ≥ 4 by showing the following a little more generalized result. The rest of this paper is organized as follows.…”
supporting
confidence: 77%
See 2 more Smart Citations
“…For Conjecture 1.2, Murphy and Nir [16], and Qian et al [18]) have confirmed this conjecture for P 4 , P 5 and k ≥ 4, we continue to confirm this conjecture for P 6 and k ≥ 4 by showing the following a little more generalized result. The rest of this paper is organized as follows.…”
supporting
confidence: 77%
“…We leave this as an open problem. It has been shown that P 2 (Simonovits [20]), P 3 (Gerbner and Palmer [11]), P 4 (Murphy and Nir [16]), P 5 (Qian et al [18]), and P 6 (Theorem 1.5) have the weak T-property. some j = i, 3 ≤ j ≤ k − 1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach where we prove that H is F -Turán-stable and use it to prove that H is F -Turán-good can also be found in [18,21,17,11]. Finally, Gerbner [13] provided the following general formulation.…”
Section: Introductionmentioning
confidence: 96%
“…Results of Gerbner [1] imply that each path is F -Turán-good for a large class of 3-chromatic graphs with color-critical edges, including odd cycles. Murphy and Nir [7] showed that P 4 is K k+1 -Turán-good. Qian, Xie and Ge [8] showed that P 5 is K k+1 -Turán-good.…”
Section: Introductionmentioning
confidence: 99%